Bridging citizen and stakeholder perspectives of sustainable mobility through practice-oriented design. Issue 1 (1st January 2019) - Hasselqvist, Hanna; Hesselgren, Mia
Abstract: Transitions toward more sustainable mobility are necessary and involve changes in complex constellations of mobility-related practices. To understand opportunities for moving in this direction, there is a need to explore both the consumption side of sustainable mobility practices and the perspective of stakeholders that provide products, services, infrastructures, and policies required for such practices. This article contributes to a discussion of critical aspects of sustainable mobility practices in relation to the responsibilities and concerns of stakeholders with power to influence these practices. We present four sets of design concepts for supporting car-free living which were formulated and co-created based on a practice-oriented analysis of a one-year study of three families in Stockholm, Sweden that replaced their cars with light electric vehicles. The design concepts bring forward elements of sustainable mobility with a focus on: trying out new mobility practices, cycling infrastructure, child-friendly public transport, and transporting stuff. Furthermore, we discussed the concepts with public and private sector stakeholders and examined their interests in particular practices. Also considered are how the responsibilities of different stakeholders may clash. Finally, we suggest that practice-oriented design concepts can support discussions and increased knowledge about responsibilities and potential conflicts related to sustainable practices, as well as provide means for supporting learning about sustainable practices among decision makers.